Kinetics of tocopherol degradation during the storage of wheat germ oil - Magariño, Micaela (2015)
Tocopherol degradation in wheat germ oil was studied during storage at different temperatures. Two types of wheat germ were used: heat-treated germ (HT) and raw germ (RG). The oil was extracted (Soxhlet, n-hexane) and stored at 25 and 47°C (82 days) and at -20 and 5°C (600 days). Tocopherols were determined by HPLC. Total tocopherol, α-tocopherol, and β-tocopherol decreased following first-order kinetics. At 25 and 47°C, the values of the degradation rate constants for total tocopherol were 5.00×10-3 days-1 (RG), 3.00×10-3 days-1 (HT), and 5.37 ×10-2 days-1 (RG), 2.57×10-2 days-1 (HT), respectively, indicating an increase in tocopherol degradation rate with increasing temperature. The reaction rates of total tocopherol were similarly affected at 5 and -20°C, with lower rate constants (4×10-4 and 2×10-4 days-1, respectively). α-tocopherol degraded faster than β-tocopherol, presenting higher rate constants. Low temperatures favour the preservation of tocopherols.